Caste, ethnicity and inequality in Nepal - Gellner, David N. (2007)
Nepal faces the danger of an all-out ethnic war breaking out in the Tarai between madhesis and parbatiyas. But, in most of the country there are so many complex and crosscutting ethnic allegiances which make a Sri Lankan-type polarisation unlikely. In the eastern Tarai, however, with its 30 per cent population of parbatiyas, there is a very real possibility that "two majorities with minority complexes" could confront each other in bloody vendettas. - Reproduced.
Keywords: Caste - Nepal; Income distribution - Nepal; Ethnic groups - Nepal; Ethnic groups